PENERAPAN TEKNOLOGI TEPAT GUNA PADA PEMBUATAN MEDIA SOSIAL (SOSMED) DI PAUD AL AMIN - Ratih Purwasih; Maisaroh; Dewi Puspitasari (Adiba Aisha Amira, 2025)
This community service activity focuses on the application of appropriate technology through the creation and management of social media at Al Amin Early Childhood Education (PAUD) in Rajabasa Lama 1 Village, Labuhan Ratu District. The program's background is the need to improve publications, information transparency, and for the Marketing and Branding of Educational Institutions. The implementation of this activity includes needs analysis, technology literacy training for teachers, the development of social media governance, and content production assistance. Data were obtained through observations, pre- and post-training questionnaires, social media data analysis, and interviews with parent representatives. The results show an increase in teachers' ability to manage technology, consistent posting, and broader access to information for the community, especially parents. The average teacher digital literacy score increased from 3.2 to 4.0 on a scale of 1–5. These findings were analyzed using the Technology Acceptance Model and Diffusion of Innovations framework, explaining that technology adoption is influenced by user perceptions of the ease of use and benefits of technology, as well as how the technology spreads within a social group. Recommendations focus on program sustainability through admin rotation, content updates, and continued digital security training.